2019
DOI: 10.3390/polym11111839
|View full text |Cite
|
Sign up to set email alerts
|

Viologen-Based Electrochromic Materials: From Small Molecules, Polymers and Composites to Their Applications

Abstract: Organic materials have gained considerable attention for electrochromic (EC) applications owing to improved EC performance and good processability. As a class of well-recognized organic EC materials, viologens have received persistent attention due to the structural versatility and property tunability, and are major active EC components for most of the marketed EC devices. Over the past two decades, extensive efforts have been made to design and synthesize different types of viologen-based materials with enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 123 publications
(171 reference statements)
0
92
0
Order By: Relevance
“…Complex 2Re(BiPy-Me) 2 containing viologen-type N-methyl-4,4'-bipyridinium ligand (MQ + ) demonstrates rich electrochemistry both in oxidation and reduction modes (Figure 8) due to availability of low lying filled and empty orbitals of the aromatic ligands and a variety of charge transfer processes, which may occur in these systems. [65][66][67][68][69][70][71][72][73][74] Application of several spectro-electrochemical techniques in the study of the [Re(N N)(CO) 3 MQ] 2 + complexes [67][68][69][70]75,76] showed that CV of this type of compounds commonly display four reversible one-electron reduction waves related to successive one and two electron reduction of the diimine and MQ…”
Section: Electrochemistrymentioning
confidence: 99%
“…Complex 2Re(BiPy-Me) 2 containing viologen-type N-methyl-4,4'-bipyridinium ligand (MQ + ) demonstrates rich electrochemistry both in oxidation and reduction modes (Figure 8) due to availability of low lying filled and empty orbitals of the aromatic ligands and a variety of charge transfer processes, which may occur in these systems. [65][66][67][68][69][70][71][72][73][74] Application of several spectro-electrochemical techniques in the study of the [Re(N N)(CO) 3 MQ] 2 + complexes [67][68][69][70]75,76] showed that CV of this type of compounds commonly display four reversible one-electron reduction waves related to successive one and two electron reduction of the diimine and MQ…”
Section: Electrochemistrymentioning
confidence: 99%
“…Thiophene, pyrrole, carbazole, viologen, triphenylamine and others are commonly used as building blocks in order to modify the electrochromic properties of the π-conjugated polymers [27][28][29][30][31][32]. Since 1986, poly(2,5-dithienylpyrrole)s (PSNS) have attracted particular interest, which could be easily synthesized via chemical and electrochemical polymerization of 2,5-dithienylpyrrole (SNS) unit [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…There is a constant increase of published research works involving viologens (see Figure 1) and this perhaps is associated with the need for new materials corresponding to a variety of hi-tech applications. The importance of viologens is reflected through the numerous review papers (many of them very recent) underlining the high versatility of this class of compounds [9,10,[12][13][14][15]. Perhaps, the most reviewed subject regarding the viologens is their electrochromism [13,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Two important classes of 4,4 -bipyridine-based products with solvatochromic and/or environment-responsive character are reviewed: viologens (i.e., N,N -disubstituted derivatives) and monoquats (i.e., monosubstituted 4,4 -bipyridine derivatives). The multifunctional nature of these derivatives is analyzed and structure-property relations are discussed in connection to the role of these derivatives in various novel applications.Molecules 2020, 25, 1 2 of 30 recent) underlining the high versatility of this class of compounds [9,10,[12][13][14][15]. Perhaps, the most reviewed subject regarding the viologens is their electrochromism [13,14,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation